The fourth dimension: A motoric perspective on the anxiety–performance relationship. Issue 1 (1st January 2016) - Carson, Howie J.; Collins, Dave
ABSTRACT: This article focuses on raising concern that anxiety–performance relationship theory has insufficiently catered for motoric issues during, primarily, closed and self-paced skill execution (e.g., long jump and javelin throw). Following a review of current theory, we address the under-consideration of motoric issues by extending the three-dimensional model put forward by Cheng, Hardy, and Markland (2009) ('Toward a three-dimensional conceptualization of performance anxiety: Rationale and initial measurement development, Psychology of Sport and Exercise, 10, 271–278). This fourth dimension, termed skill establishment, comprises the level and consistency of movement automaticity together with a performer's confidence in this specific process, as providing a degree of robustness against negative anxiety effects. To exemplify this motoric influence, we then offer insight regarding current theories' misrepresentation that a self-focus of attention toward an already well-learned skill always leads to a negative performance effect. In doing so, we draw upon applied literature to distinguish between positive and negative self-foci and suggest that on what and how a performer directs their attention is crucial to the interaction with skill establishment and, therefore, performance. Finally, implications for skill acquisition research are provided. Accordingly, we suggest a positive potential flow from applied/translational to fundamental/theory-generating research in sport which can serve to freshen and usefully redirect investigation into this long-considered but still insufficiently understood concept.